Penggunaan Technology Acceptance Model Untuk Menganalisis Behavioural Intention Mahasiswa Dalam Menggunakan E-Learning - Vidyanata, Deandra (Universitas Negeri Surabaya, 2021)
In this technological era, there is a certain needs for student to access learning materials without any time or space boundaries. Thus, adopting an online learning platform is no longer a choice but a necessity. There are many benefits provided by the implementation of online learning system, such as learning flexibility, reducing cost, etc. Nevertheless, there is certain challenge associated with the users acceptance of technology. In this paper, we take Technology Acceptance Model as a foundation to analyze students intention to use the online learning system.The population of this study is the freshmen of IBM Universitas Ciputra Surabaya. Sampling technique used in this study is simple random sampling with the result is 215 respondents as the sample. The result shows there is a significant relationship between perceived ease of use and perceived usefulness to students attitude to use online learning system . In addition, students attitude to use online learning system has a significant influence towards their intention to use e-learning.